New species of Thyasira, Mendicula, and Axinulus (Bivalvia, Thyasiroidea) from Sub-Antarctic and Antarctic waters - Zelaya, Diego Gabriel (Polar Biology)
Three new thyasirid species from the Sub-Antarctic and Antarctic waters are described: Thyasira patagonica, Mendicula sudamericana, and Axinulus antarcticus. T. patagonica is characterized by its strong commarginal sculpture, shell as height as length or higher than long, posterior auricle delimited by a deep submarginal sulcus, and a long and sloping straight anterior half of dorsal margin. M. sudamericana distinguished by its longer than high shell outline, elongated tooth-like enlargement anterior to beak, gills with only one demibranch at each side, and foot with a marked heel. A. antarcticus has aminute, subquadrate shell, hinge with a small swelling anterior to beak, gills with a single demibranch, and the lateral body pouch elongated and almost smooth. The present study provides the first reliable record of thyasirids, with a single demibranch from the Southern Ocean. Moreover, characters for a better definition of Mendicula are provided. Fil: Zelaya, Diego Gabriel. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Zoología Invertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina